HUBUNGAN ANTARA SHYNESS DENGAN SELF-ESTEEM PADA DEWASA AWAL YANG TIDAK BEKERJA DI KOTA MAKASSAR - Rezqyawan, Nandhika; Ridfah, Ahmad; Syam, Rahmawati (JIVA: Journal of Behaviour and Mental Health, 2024)
ABSTRACTSelf-esteem really supports early adult individuals in getting a job, but most individuals who have entered the early adulthood phase still feel ashamed of themselves and their surroundings, making it difficult to get a job. This research aims to determine the relationship between shyness and self-esteem in young adults who do not work in Makassar City. The sample consisted of 402 respondents. The data collection technique was carried out using the instruments (1) shyness scale and (2) self-esteem scale. The technique used in hypothesis testing is the non-parametric statistic Kruskal-Wallis test. The results of the research show that 1) there is a negative relationship between shyness and self-esteem in young adults who do not work in the city of Makassar, 2) based on the results of hypothesis testing, the correlation coefficient value is -0.204 with a p value of 0.000, which means the shyness variable has a negative relationship with self-esteem. So the lower an individual's shyness, the greater the individual's self-esteem. Based on this, it can be concluded that there is a negative relationship between shyness and self-esteem in young adults who have not worked in Makassar City. The implications of this research provide a positive outlook for individuals who are not working so they can increase self-esteem and reduce shyness so they are more productive.Keywords: Self-esteem, Shyness, Young Adults ABSTRAKSelf-esteem sangat menunjang individu dewasa awal untuk mendapatkan pekerjaan namun kebanyakan individu yang sudah menginjak fase dewasa awal masih merasa malu dengan dirinya sendiri dan lingkungan sekitar sehingga sulit mendapatkan pekerjaan. Penelitian ini bertujuan untuk mengetahui hubungan antara shyness dengan self-esteem pada dewasa awal yang tidak bekerja di Kota Makassar. Sampel berjumlah 402 responden adapun teknik pengumpulan data dilakukan dengan menggunakan instrumen (1) skala shyness dan (2) skala self-esteem. Teknik yang digunakan dalam uji hipotesis adalah statistik non parametrik uji kruskal-wallis. Hasil penelitian menunjukkan bahwa 1) ada hubungan negatif antara shyness dengan self-esteem pada dewasa awal yang tidak bekerja di kota Makassar, 2) berdasarkan hasil uji hipotesis nilai koefisien korelasi sebesar -0,204 dengan nilai p sebesar 0,000 yang berarti variabel shyness memiliki hubungan negatif dengan self-esteem. Sehingga semakin rendah shyness individu maka semakin meningkat self-esteem yang dimiliki oleh individu. Berdasarkan hal tersebut maka disimpulkan bahwa terdapat hubungan negatif shyness dengan self-esteem pada dewasa awal yang belum bekerja di Kota Makassar. Implikasi penelitian ini memberikan pandangan positif bagi individu yang tidak bekerja agar mampu meningkatkan self-esteem dan menurunkan  shyness sehingga lebih produktif.Kata Kunci: Dewasa awal, Self-esteem, Shyness